2006
DOI: 10.1111/j.1440-1843.2006.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Early switch to oral antibiotics and early discharge guidelines in the management of community‐acquired pneumonia

Abstract: The use of early switch and early discharge guidelines for CAP reduced the duration of i.v. antibiotics and LOS while maintaining high levels of safety and patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 16 publications
2
21
1
3
Order By: Relevance
“…Second, we included patients who received prolonged treatment even after improvement in condition, because the criterion for discontinuing antibiotic treatment after switch therapy was not determined. Third, our study showed more prolonged LOS compared to other reports (7,9,23 T a b l e 5 . Co mp a r i s o n o f L e n g t h o f Ho s p i t a l S t a y , Ho s p i t a l Ch a r g e s , T …”
Section: T a B L E 4 An T I B I O T I C S F O R S Wi T C H T H E R contrasting
confidence: 54%
“…Second, we included patients who received prolonged treatment even after improvement in condition, because the criterion for discontinuing antibiotic treatment after switch therapy was not determined. Third, our study showed more prolonged LOS compared to other reports (7,9,23 T a b l e 5 . Co mp a r i s o n o f L e n g t h o f Ho s p i t a l S t a y , Ho s p i t a l Ch a r g e s , T …”
Section: T a B L E 4 An T I B I O T I C S F O R S Wi T C H T H E R contrasting
confidence: 54%
“…Hospitalized patients with severe community-acquired infections should be treated initially with parenteral agents and could be switched to oral therapy when the clinical status improves. This switch therapy is gaining acceptance as a means of facilitating early discharge of patients from the hospital and reducing the overall costs of antimicrobial therapy (6)(7)(8). In the case of our 2-aryl carbapenems, this treatment strategy for community-acquired infections could also contribute to preserving the therapeutic efficacy of existing antipseudomonal carbapenems, which are key antibiotics for hospital-acquired infections.…”
Section: Discussionmentioning
confidence: 99%
“…Combinational development of parenteral and oral formulations of the same new class carbapenem, allowing a switch from parenteral to oral treatment, could contribute to early hospital discharge, decrease the cost of treatment (6)(7)(8), and reduce the risk of selection for cross-resistance to existing parenteral carbapenems in nosocomial pathogens.…”
mentioning
confidence: 99%
“…Once a patient is admitted for CAP, LOS is determined mostly by the duration of therapy [70]. Duration of therapy is extremely variable and many times not based on evidence.…”
Section: Clinical Parameters For Dischargementioning
confidence: 99%
“…These criteria included resolution of respiratory symptoms, resolution of fever, ability to tolerate oral antibiotics, normalizing white blood cell count, hemodynamic stability, stable or improving chest x-ray, stable comorbid diseases, baseline mental status, and no other sites of infection. A prospective study performed in 2007 showed a reduction in LOS of 0.74 days with no significant mortality events when several of these criteria were implemented [70]. Importantly, a high level of patient satisfaction was also achieved.…”
Section: Clinical Parameters For Dischargementioning
confidence: 99%